Peran Koordinator dalam Menekan Agresivitas Suporter - Asep Singgih Wijanarko; Indra Wahyudi; Dewi Handayani Harahap (Jurnal Psikologi, 2021)
Football is a very popular sport in the world. Most of people tend to glorify their own football team. Those supporters are more likely fanatic. They tend to obtrude aggressively that their football team should win in every competition. When their team loses in a competition, the supporters tend to be angry. They are unable to accept that their team could be lost in a game. As a result they attack every object to discharge their aggressiveness. They are hooligan. In order to muffle their aggressiveness, an obeyed supporter coordinator is urgently needed. This qualitative research attempts to explore the coordinator role in muffling those supporters. Two coordinators and two supporters participated in this research. They are from the blue face and the blue capital supporter clubs. The interview list is conducted base on 6 aspects i.e. supporter’s expectation, norm, performance, evaluation sanction and power. This research revealed that a coordinator’s instruction will be obeyed when he or she is a wise model and able to display good behaviors. The coordinator’s advices have also been complied since he or she is good in influencing those supporters. Because of this thoughtful coordinator, the supporters’ aggressiveness can be handled well.